Vascularized Dartos Flap in Conjunction with Tubularized Incised Plate Urethroplasty: Single versus Double Flaps for Management of Distal Hypospadias - Safwat, Ayman (S. Karger AG, 2012)
OBJECTIVE: To compare the results of Snodgrass repair with single versus double vascularized dartos pedicle flap for neouretheral coverage. PATIENTS AND METHODS: Fifty-eight pediatric patients with mean age 41.5 ± 21 months (range 9–96 months) underwent primary hypospadias repair, 39 uncircumcised and 19 circumcised, classified into 2 groups according to coverage of the neourethra. Single layer coverage (Group I) was performed in 28 (48.3%) while double layers coverage (Group II) was done in 30 (51.7%) cases. RESULTS: After mean follow-up 8.6 ± 5.4 months (range 3–24 months), good cosmetic results with vertical slit like meatus at the tip of conical shaped glans were obtained in 53 cases (91.4%). Totally 5 cases occurred postoperative complications, of which 4 cases in Group I [2 (7.1%) with urethrocutaneous fistula, 1 (3.6%) with meatal stenosis and 1 (3.6%) with skin necrosis], 1 case in Group II [glanular dehiscence (3.3%)]. No fistula was observed in Group II. CONCLUSION: The Snodgrass tubularized incised-plate repair in conjunction with double layer coverage of the neourethra could be considered the procedure of choice for distal hypospadias with low complications rate especially urethrocutaneous fistula.